Intra-Articular Osteoid Osteoma: Radiological Manifestations. Issue 1 (6th May 2020) - Chatt, Najoi; Docquier, Pierre-Louis; Dumitriu, Dana
We report a case of intra-articular osteoid osteoma (IAOO) of the elbow, in order to point out the clinical and imaging features which made the case challenging and caused a diagnostic delay.